Does Inclusion of Mental Agility Test in Admission Exam Help Better Student Selection in the Health Professions Education Programs? - Maharjan, Babu Raja; Bhandary, Shital; Shrestha, Shrijana; Gongal, Rajesh (Journal of Nepal Health Research Council, 2022)
Academic ability test has been used predominantly in student selection of medical and allied health profession education programs in Nepal. But the use of academic performance as the single selection criterion puts the students from low socioeconomic background at greater disadvantage despite equal suitability due to the lack of adequate guidance and support during their schooling. To address this limitation, use of aptitude test i.e. both the general cognitive and non-cognitive ability tests that measures fluid intelligence and personality traits respectively has been practiced. The measurement of non-cognitive traits has been found to predict the clinical examination score. In Nepal, for the first time, Patan Academy of Health Sciences implemented the assessment of aptitude test (both cognitive and non-cognitive ability test) for the student selection in the undergraduate medical program. Since the inception, Medical Education Commission in Nepal embraced Mental Agility Test, a component of an aptitude test, along with the academic ability test for the nationwide common entrance test in all the undergraduate Health Professions Education Programs. This indeed is an innovative approach in student selection, but in the context of Nepal whether the use of these tools is appropriate in the entrance exam requires psychometric evaluation and further validation through graduates’ performance after their enrolment.Keywords: Health professions education; mental agility test; student selection.